EFFICIENT VALIDATED METHOD OF HPLC TO DETERMINE ENALAPRIL IN COMBINATED DOSAGE FORM CONTAINING ENALAPRIL AND BISOPROLOL AND IN VITRO DISSOLUTION STUDIES - Logoyda, Liliya (International Journal of Applied Pharmaceutics, 2019)
Objective: A rapid and reproducible HPLC method has been developed for the determination of enalapril in experimental combined dosage forms containing bisoprolol and enalapril and for drug dissolution studies. Methods: The separation was done using a column Hi Qsil C18 (4.6х250 mm, 5 μm particle size) and a mobile phase of methanol: phosphate buffer solution (65:35, v/v), flow-rate of 1.0 ml/min. The injection volume was 300 μL and the ultraviolet detector was set at 225 nm. Results: The method was validated as per ICH guidelines. Under these conditions, enalapril was eluted at 5.33 min. Total run time was shorter than 6 min. A linear relationship between the concentration and the area of ​​chromatographic peaks of enalapril in the range of 1.250 mg/ml–10.000 mg/ml (7.500 mg/ml at pH 1.2) was established. Requirements for linear dependency parameters are performed in this case throughout the range of application of the technique. Linearity studies were conducted in a wide range of concentrations (25-200% at pH 4.5 and 6.8, 25-150% at pH 1.2). In the medium with pH 1.2 release of enalapril from tablets in 5 min is 83.38 %, after 15 min-94.11%, after 30 min-97.17 %; in medium with pH 4.5 the release of enalapril from tablets in 5 min makes 47.13 %, after 15 min-88.34 %, after 30 min-95.86 %; in a medium with pH 6.8, the release of enalapril from tablets in 5 min is 71.04 %, and after 15 min-88.88 %, after 30 min-92.11 %. Conclusion: A simple and sensitive HPLC method was developed for the estimation of enalapril in tablets containing enalapril and bisoprolol. The proposed method was applied successfully for quality control assay of enalapril in experimental tablets and in vitro dissolution studies.